Development and validation of the Decisional Balance Scale for Physical Activity in Female Survivors of Violence (DBSPA-FSV) - Favola, Camille; d'Arripe-Longueville, Fabienne; Piroird, Lou-Anne; Hayotte, Meggy; Mériaux-Scoffier, Stéphanie (Frontiers in Public Health, 2025)
IntroductionDue to the trauma they have experienced, women who are survivors of violence struggle to engage in regular physical activity despite its numerous benefits. Identifying the factors that facilitate or hinder engagement in physical activity within this population is therefore essential. However, no valid tool currently exists specifically for this purpose. This study, based on the concept of decisional balance drawn from the transtheoretical model of behavior change, aimed to develop and validate the Decisional Balance Scale for Physical Activity in Female Survivors of Violence (DBSPA-FSV).MethodsThree hundred one volunteers participated in three complementary steps which followed established validation procedures. In step 1, a preliminary version of the items was developed based on the existing literature. In step 2, the dimensionality and convergent validity of the scale were examined. In step 3, the reliability of the scale was tested.ResultsIn step 1, a preliminary version of 32 items was developed. The scale was refined to 22 items, grouped into two factors (facilitators and barriers) and six sub-dimensions (physical, psychological, and socio-environmental). In step 2, bi-factor confirmatory models with a global construct and six or two correlated factors demonstrated satisfactory fit indexes. Convergent validity was confirmed by significant correlations between DBSPA- FSV constructs and the concept of self-determined motivation in the expected directions. In step 3, the internal and test-retest reliability of the scale were confirmed.DiscussionThe DBSPA-FSV scale exhibits satisfactory psychometric properties and will contribute to research on the engagement in physical activity of women survivors of violence.